Identifikasi Tingkat Kerawanan Tanah Longsor di Provinsi Sulawesi Tengah - Sunardi; Nurmasyita Anggraini; Solih Alfiandy; Asep Firman Ilahi (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2022)
The Landslide disaster is an event that is associated with various types of factors such as precipitation, geology, distance from the fault, vegetation, and topography. The Central Sulawesi region is an area that has many hills and mountains as well as sandy soil types with a total annual rainfall that varies due to geographical location and topographical conditions which make this region have a type of rain which is dominated by local dry types and very dry or wet to very wet, so it is interesting to be used as a research area. Based on the background of the problems that have been described, this study aims to determine areas that are prone to landslides in Central Sulawesi Province. The types of data used to determine the level of vulnerability to landslides are rainfall, rock type, slope, land cover and soil type. The mapping system used is geographic information system (GIS) software with a weighted overlay method. The results showed that the level of vulnerability to landslides in the Central Sulawesi region was dominated by the moderate level of vulnerability. Based on the research results, it can be concluded that landslides will occur if the values of all the factors (parameters) that cause them are met.